Proposing an improved cyclic plasticity material model for assessment of multiaxial response of low C-Mn steel. (January 2021) - Arora, Punit; Samal, Mahendra K.; Gupta, Suneel K.; Chattopadhyay, J.
Graphical abstract: Highlights: Validation of current cyclic plasticity material models w.r.t. limited loading cases. Low C-Mn steel showed Masing behavior with linear shift for uniaxial/ in-phase cases. Chaboche model under-predicts axial and shear stress for non-proportional (NP) cases. Chaboche-Tanaka-Meggiolaro (CTM) model results in better predictions for few NP cases. Proposed modification in CTM model results in improved simulations for all NP cases. Abstract: Present work is aimed at validation of existing popular cyclic plasticity material models and proposing an improved model for SA 333 Gr. 6 material. Recently reported in-house axial-torsion tests have been used for validation. Present analyses considered Chaboche's non-linear kinematic hardening rule, Tanaka's fourth order tensor and Meggiolaro's non-proportionality considerations. The Chaboche-Tanaka-Meggiolaro model resulted in comparable assessments for stabilized loops under uniaxial, proportional and few non-proportional conditions. However, the axial stress response under most of non-proportional conditions was significantly under-predicted. The proposed modification in dynamic recovery term of kinematic hardening rule resulted in improved assessments for nearly all strain paths.